The prehistory and reception of Leonard Bernstein’s Missa Brevis (1988) - Dittamo, Patrick Connor (Kansas State University, 2019)
Leonard Bernstein (1918-1990) commonly repurposed previously-written material in new compositions, including his Missa Brevis (1988), which adapted significant portions of his incidental music for Lillian Hellman’s play The Lark (1955), itself an adaptation of French playwright Jean Anouilh’s play L’Alouette (1953) about the trial of Joan of Arc. Based on an assessment of The Lark’s mixed reception history as a play, Bernstein’s score, recorded by the New York Pro Musica, deserves some credit for the original Broadway run’s considerable success. Bernstein’s Medieval- and Renaissance-inflected score was written shortly before the play’s tryout run in Boston, and used fragments of verse by Adam de la Halle (c. 1245-1288/1306) and Jean-Antoine de Baïf (1532-1589), as well as the tune of the French folksong “Plantons la Vigne,” and not the commonly-cited “Vive la Grappe.” Bernstein and the New York Pro Musica were well- compensated for their contributions to The Lark; however, during the play’s national tour, there was a pay dispute over reduced royalties between Bernstein’s agent and the play’s management. Before the New York premiere of The Lark, Bernstein expressed a belief that its incidental score held a viable “kernel of a short mass,” and considered using a Lark-based missa brevis to fulfill a commission for Juilliard’s fiftieth anniversary, an idea he ultimately abandoned. This idea was in his mind before the eminent conductor Robert Shaw attended a performance of the play. The traditional account that the idea was brought to him by Shaw is not borne out by the available evidence, although Shaw did approach Bernstein about programming the Lark choruses for a concert tour, an idea that was also abandoned. The subsequent Missa Brevis commissioned by the Atlanta Symphony for Shaw’s retirement in 1988 was a substitute for an orchestral work originally requested in 1983, and is almost a straight contrafactum of music from the original Lark score, with some fine-tuning of interpretive markings. The Missa Brevis was expanded to utilize the full liturgical Ordinary text, sans Credo, by Bernstein’s musical assistant George Steel, and was published in 1990. While the Missa Brevis is not typical of Bernstein’s oeuvre, recordings in recent years have garnered moderate praise from reviewers.
Keywords: Leonard Bernstein; Lillian Hellman; Robert Shaw; Lark; Missa Brevis; New York Pro Musica